Pengelolaan Keuangan Dalam Administrasi Pendidikan - Matondang, Aflah Husnaini; Purba, Bintang Mahrani; Harahap, Novia Rahmadani (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
Financial management in educational administration has a very important role in increasing the effectiveness of the teaching and learning process in educational institutions. The research method used in this research is a qualitative research method with literature study. The research results show that the challenges faced in financial management, such as budget uncertainty and fluctuations in operational costs, require good financial education and training for education stakeholders. Therefore, a deep understanding of the financial sector in educational administration is crucial to achieving optimal educational goals.